Community Mitigation Climate Change at Household Waste Management - Yaskinul Anwar; Samsul Alam (Pusat Kajian Berkelanjutan UIN Sulthan Thaha Saifuddin Jambi, 2024)
Climate change is a concern in the world because of its threat to the environment. Household waste management can be done through mitigation to the community to reduce household waste, which causes methane gas emissions, climate change, and an increase in the volume of waste. This study aims to determine community mitigation in climate change in household waste management in Samarinda City and to determine community participation in implementing the climate village program in Samarinda City. This study is a descriptive study with a qualitative approach. The population in this study were all communities and ProKlim administrators in 5 research locations with purposive sampling and saturated sampling techniques with 35 informants. The sampling technique is interviews, observations, and documentation. The results of the study from 5 Proklims show that the community has carried out mitigation in their waste management to reduce carbon emissions and maintain their living environment. Forms of community mitigation include sorting and saving waste in waste banks in climate village groups. In addition, the community also reuses plastic waste that can be reused and makes compost from organic waste and recycles waste. Community participation in ProKlim is very supportive by participating in the activities, but some informants did not participate because ProKlim was not yet active.